The roles of urban heritage in determining the image of the royal town of Sri Menanti, Negeri Sembilan - Harun, Nor Zalina; Fairuz, Dg Norhidayah; Nordin, Nor Adilla (Malaysian Institute of Planners, 2015)
Malaysia has many towns of historic and cultural significance that are worthy of preservation for sustainable development. For instance, a royal town, which is a town where the old palaces and the royal administrative district are located. This paper aims to discover the significance of the urban heritage of a royal town so as to ensure its preservation. Special attention is paid to the identification of townscape elements in forming the image of the town and the roles of the townscape elements as built heritage of the royal town. A case study was carried out in Sri Menanti, Negeri Sembilan, which is one of the royal towns in Malaysia. The study methodology involves a historical map overlay, non-participant observation and semi-structured interviews. The findings reveal that Sri Menanti has played a significant role in the history and development of Negeri Sembilan. Additionally, the contribution of 'Adat Perpatih' to the nation's history as one of the unique administrative components helps to signify the importance of the town's local culture and urban heritage. The town also represents a number of townscape elements that are intertwined as urban heritage, with rich cultural and architectural significance. The paper concludes that diversity in the character of the town is unique and worthy of preservation